Anthropometric and musculoskeletal gender differences in young soccer players - Taketomi, S.; Kawaguchi, K.; Mizutani, Y.; Yamagami, R.; Sameshima, S.; Takei, S.; Kono, K.; Inui, H.; Tanaka, S.; Haga, N. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: This study aimed to clarify potential gender differences across a comprehensive set of anthropometric and musculoskeletal characteristics within a young soccer player population. METHODS: This study included 227 (121 males and 106 females with mean ages of 19.0 and 17.5 years, respectively) young elite soccer players. Anthropometric measurements were obtained. In addition, general joint laxity tests assessing the wrist, elbow, shoulder, trunk, hip, knee, and ankle were performed. Muscle flexibility tests were performed on the iliopsoas, quadriceps femoris, hamstring, gastrocnemius, and soleus muscles. Moreover, isometric knee extension and flexion strength and isometric hip abduction strength were measured. Single- and double-leg balance tests were also performed. RESULTS: Male soccer players were taller, heavier, and had lower fat mass and percent body fat, and greater skeletal muscle mass and body minerals than female soccer players. Female soccer players had significantly greater laxity in all tests for general joint laxity. Female soccer players demonstrated significantly better hamstring and soleus flexibility than male soccer players but worse iliopsoas flexibility. Consequently, no significant differences were noticed in the quadriceps and gastrocnemius muscles between the male and female soccer players. However, female soccer players demonstrated significantly weaker knee extension and flexion and hip abduction. The hamstring- quadriceps ratio was significantly lower in female soccer players. Although no significant difference exists in the center of pressure excursion in the double-leg balance test between male and female soccer players, female soccer players displayed a significantly lower center of pressure excursion in the single-leg balance test. CONCLUSIONS: Young male and female soccer players demonstrate significantly different anthropometric and musculoskeletal profiles.